ENABLING AND SUSTAINING SHARED LEADERSHIP IN AUTONOMOUS TEAMS - Hess, James P. (European Scientific Journal, ESJ, 2015)
A proliferation of autonomous teams across industries entices researchers to examine the transformation of emergent leadership into sustainable shared leadership as an optimal condition for team effectiveness. Little, if any, in-depth research has surfaced in the literature to explain shared leadership. Therefore, the purpose of this study was to examine specific organizational dynamics most likely to enable and sustain shared leadership in autonomous teams. In this exploratory study, empirical feedback representing personal team experiences of 18 autonomous team members was collected and arranged in themes. What resulted was evidence that top-leader support, an institution-wide focus on team outcomes, face-toface communication and frequent feedback, and equity in team-member recruitment processes were perceived to be the most critical organizational dynamics shaping shared leadership in autonomous teams.